Identification and functional analysis of an ovarian form of the egg activation factor phospholipase C Zeta (PLCζ) in pufferfish. - Coward, K; Ponting, C; Zhang, N; Young, C; Huang, C; Chou, C; Kashir, J; Fissore, R; Parrington, J (2010)
Recent studies suggest that egg activation in mammals is triggered by a sperm-specific phospholipase C, PLCzeta. In other vertebrate species such as medaka fish, chickens, and quail, PLCzeta is also expressed as a testis-specific mRNA. Functional studies suggest that PLCzeta plays a similar role as a trigger of egg activation in these species. Here, we report the identification of PLCzeta orthologues in pufferfish species Takifugu rubripes (Fugu) and Tetraodon nigroviridis (Tetraodon). Unexpectedly in these species PLCzeta is expressed not in the testis, but in ovary and brain. Injection of pufferfish PLCzeta copy ribonucleic acid (cRNA) into mouse eggs failed to trigger calcium oscillations, unlike medaka PLCzeta cRNA. Our findings provide the first evidence that PLCzeta may be expressed in the egg, rather than the sperm, in some vertebrate species, and that its mechanism of action and physiologic role at fertilization may differ in different vertebrate species. Mol. Reprod. Dev. © 2010 Wiley-Liss, Inc.